2019
DOI: 10.1002/bbb.2047
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal liquefaction of macroalgae for the production of renewable biofuels

Abstract: In all biorefinery systems, excess water represents a key challenge, and its removal by drying is often a necessary and crucial pre-treatment. Second-generation feedstocks have often fallen at this hurdle, particularly microalgae-derived biomasses, which require extensive (and costly) dewatering. Hydrothermal liquefaction (HTL) has gained increasing attention in recent years as a technology that uses the water present in the feedstock as a versatile reaction medium, which functions as a solvent, reactant, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…It can be seen that a reaction time beyond 30 min is found to be unfavorable for the CBO yield. This limit of reaction time was stressed by Raikova et al to be 15 min. This difference can be ascribed to the other parameters including the biochemical composition of the alga biomass and reaction temperature.…”
Section: Hydrothermal Liquefaction Of Algaementioning
confidence: 97%
See 2 more Smart Citations
“…It can be seen that a reaction time beyond 30 min is found to be unfavorable for the CBO yield. This limit of reaction time was stressed by Raikova et al to be 15 min. This difference can be ascribed to the other parameters including the biochemical composition of the alga biomass and reaction temperature.…”
Section: Hydrothermal Liquefaction Of Algaementioning
confidence: 97%
“…80 It should be noted that heating rates, reaction times, and reaction temperatures are closely related and inseparable from each other, and thus, slow heating (and cooling) rates lead to long reaction times. 87 High reaction temperatures required a longer heating period. It can be seen that a lower initial pressure is favorable for a high yield of CBO.…”
Section: Algae Species: Characteristics and Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave assisted HTL has also been examined [109], as has the application of HTL using macroalgae [110]. However, the economy of the process is still questionable due to the utilization of higher pressure conditions.…”
Section: Hydrothermal Liquefactionmentioning
confidence: 99%
“…9 Several authors have demonstrated that macroalgae can be used in the hydrothermal liquefaction process. 10 Raikova et al presented a comprehensive study on a broad range of macroalgae species from the UK and the ideal hydrothermal liquefaction conditions to convert these into bio-crude and nutrient partition into the aqueous phase. 11 In a further study the authors also combined plastics present in the ocean with the macroalgae demonstrating that this led to a higher biocrude heating value.…”
Section: Introductionmentioning
confidence: 99%